Synbiotics in caries prevention: A scoping review. - Mohammed Nadeem Bijle; Manikandan Ekambaram; Edward C M Lo; Cynthia Kar Yung Yiu (PLoS ONE)
The scoping review aimed to examine the evidence on the role of synbiotics in caries prevention. PubMed, SCOPUS, and Web of Science databases search were performed. Any in vitro study, clinical trial, systematic review with/without meta-analysis, umbrella review/meta-evaluation, narrative review addressing the role of synbiotics in caries prevention were included in the scoping review. Data were extracted from the included studies using pre-approved registered protocol. Twenty-eight records were identified, of which 5 in vitro studies, 1 quasi-experimental clinical trial and 1 narrative review were included in the present review. No controlled clinical trials or systematic reviews on the role of synbiotics in caries prevention could be identified. Except 1, all in vitro studies examined the combined effect of saccharides and lactobacilli spp. as potential synbiotics on the growth of Streptococcus mutans. However, the proposed synbiotics in 4 in vitro studies either did not qualify or remained ambiguous of its eligibility as a potential synbiotic for caries prevention. One recent in vitro study explored the possibility of L-arginine and Lactobacillus rhamnosus GG synbiotic for caries prevention. The quasi-experimental clinical study without a control arm did not explicitly mention the intervention composition and thus, its synbiotic potential remains unclear. A narrative review highlighted the potential of combining arginine (prebiotic) with arginolytic bacteria (probiotic) as a synbiotic, which appears promising for caries prevention. The eligibility of the proposed synbiotics as a true synbiotic needs to be carefully addressed. Due to a lack of controlled clinical studies on synbiotics for caries prevention, evidence on their caries-preventive potential is weak. Future studies are needed to examine the combination of amino acids (esp. arginine) with probiotics as a potential synbiotic against cariogenic pathogens.